Heart Rate Variability in Young Adults with Bronchial Asthma with and without Previous COVID-19 Infection: A Cross-sectional Study - Gunaseelan Deivendran; Thamarai Selvi Kanagaraj; Bhavisha Sreenivasan Leelabai; Nalini Jayanthi; Saravanan Ayyavoo (Journal of Clinical and Diagnostic Research)
Introduction: Heart Rate Variability (HRV) is a validated, non invasive measure of Autonomic Nervous System (ANS) function. Both bronchial asthma and post Coronavirus Disease-2019 (COVID-19) syndrome are independently associated with autonomic dysregulation. However, the combined impact of asthma and prior COVID-19 infection on HRV in young adults remains underexplored. Aim: To compare HRV parameters between young adult bronchial asthma patients with and without a history of COVID-19, and assess the extent of autonomic dysfunction attributable to COVID-19. Materials and Methods: This cross-sectional study included 100 bronchial asthma patients aged 20-40 years, equally divided into two groups based on COVID-19 history. Standardised HRV recordings were obtained in the supine position following a 15-minute rest period. HRV was assessed using time domain indices- Standard Deviation of NN intervals (SDNN) and Root Mean Square of Successive Differences (RMSSD)- and frequency domain indices- Low Frequency (LF), High Frequency (HF), and LF to HF ratio (LF/HF ratio)- using Kubios HRV software. Haemodynamic parameters including Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), and Pulse Rate (PR) were also compared. Statistical analysis was performed using One-way Analysis of Variance (ANOVA) and independent t-tests, with a p-value of less than 0.05 considered statistically significant. Results: Asthma patients with prior COVID-19 infection demonstrated significantly higher DBP (84.48±7.38 vs. 79.12±6.22 mmHg; p<0.001) and PR (88.38±10.48 vs. 79.88±9.74 bpm; p<0.001). HRV analysis revealed significantly lower SDNN (30.18±5.18 vs. 33.54±6.27 ms; p=0.002), RMSSD (23.80±4.72 vs. 28.00±5.54 ms; p<0.001), and HF power (92.54±11.67 vs. 115.48±17.53 ms2; p<0.001) in the post COVID group, along with elevated LF power (232.76±24.62 vs. 193.32±20.28 ms2; p<0.001) and LF/HF ratio (2.52±0.32 vs. 1.67±0.23; p<0.001), suggesting heightened sympathetic activity and reduced vagal modulation. Conclusion: Asthma patients with prior COVID-19 infection exhibit significant autonomic dysfunction marked by reduced parasympathetic modulation and heightened sympathetic dominance. These findings highlight the importance of cardiovascular autonomic assessment in asthma patients recovering from COVID-19, particularly for early identification of dysautonomia and cardiovascular risk stratification.